BRK1, a Bub1-Related Kinase, Is Essential for Generating Proper Tension between Homologous Kinetochores at Metaphase I of Rice Meiosis([W]) - Wang, Mo (American Society of Plant Biologists, 2012)
Bub1 (for budding uninhibited by benzimidazole 1), one of the main spindle checkpoint kinases, acts as a kinetochore scaffold for assembling other checkpoint proteins. Here, we identify a plant Bub1-related kinase 1 (BRK1) in rice (Oryza sativa). The brk1 mutants are sterile due to the precocious separation of sister chromatids at the onset of anaphase I. The centromeric recruitment of SHUGOSHIN1 and phosphorylation of histone H2A at Thr-134 (H2A-pT134) depend on BRK1. Although the homologs can faithfully separate from each other at the end of meiosis I, the uncorrected merotelic attachment of paired sister kinetochores at the early stage of metaphase I in brk1 reduces the tension across homologous kinetochores, causes the metaphase I spindle to be aberrantly shaped, and subsequently affects the synchronicity of homolog separation at the onset of anaphase I. In addition, the phosphorylation of inner centromeric histone H3 at Ser-10 (H3-pS10) during diakinesis depends on BRK1. Therefore, we speculate that BRK1 may be required for normal localization of Aurora kinase before the onset of metaphase I, which is responsible for correcting the merotelic attachment.